Gut microbiota alteration in adolescent anorexia nervosa does not normalize with short‐term weight restoration. Issue 6 (12th December 2020) - Schulz, Nina; Belheouane, Meriem; Dahmen, Brigitte; Ruan, Vanessa A.; Specht, Hannah E.; Dempfle, Astrid; Herpertz‐Dahlmann, Beate; Baines, John F.; Seitz, Jochen
Abstract: Objective: Gut microbiota are linked to metabolic function, body weight regulation, and brain and behavioral changes. Alteration of gut microbiota is repeatedly demonstrated in adults with anorexia nervosa (AN) and transplantation of stool from adult patients with AN reduces weight gain, food consumption and food efficiency in germ‐free mice. No similar data are available for adolescents, who might differ from adults due to their shorter duration of illness. Method: Nineteen female adolescent patients with AN at admission and after short‐term weight recovery were included in a longitudinal study and compared to 20 healthy controls (HC). DNA was extracted from stool samples and subjected to 16S rRNA gene sequencing and analysis. Group comparisons, indicator genera and simper analysis were applied. Taxon abundances at admission was used to predict inpatient treatment duration. Results: Alpha diversity is increased in patients with AN after short‐term weight recovery, while beta diversity shows clear group differences with HC before and after weight gain. A reduction in Romboutsia and taxa belonging to Enterobacteriaceae at both timepoints and an increase in taxa belonging to Lachnospiraceae at discharge are most indicative of patients. Lachnospiraceae abundance at admission helped to predict shorter inpatient treatment duration. Discussion: This pilot study provides first evidence of gut microbiota alterations in adolescent patients with AN that do not normalize with weight gain. If verified in larger studies, the predictive power of taxa belonging to Lachnospiraceae for clinical outcome could complement known predictors at admission, inform clinicians and serve as a target for nutritional interventions.